2018
DOI: 10.1111/idj.12402
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of head and neck cancer – a multicentre survey among young respondents in Poland

Abstract: The level of HNC cancer awareness in the young population is alarmingly low. A large number of non-medical students are unaware of risk factors and early symptoms. Educational campaigns aimed at effective prophylaxis, earlier diagnosis and treatment of HNC are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
5
10
3
Order By: Relevance
“…In the conducted study, 92.6% of standard high school students and 82% of technical school students indicated smoking as one of the main HNCs risk factors. Krentowska et al (2018) showed insu cient awareness among all non-medical school students compared to medical students, a similar trend was observed in the conducted study (when comparing students of scienti c and non-scienti c curriculums). 34% of high school students consider alcohol to be an oral cancer risk factor and 22% say that HPV infections have an impact on HNCs development [13].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the conducted study, 92.6% of standard high school students and 82% of technical school students indicated smoking as one of the main HNCs risk factors. Krentowska et al (2018) showed insu cient awareness among all non-medical school students compared to medical students, a similar trend was observed in the conducted study (when comparing students of scienti c and non-scienti c curriculums). 34% of high school students consider alcohol to be an oral cancer risk factor and 22% say that HPV infections have an impact on HNCs development [13].…”
Section: Discussionsupporting
confidence: 86%
“…Krentowska et al (2018) showed insu cient awareness among all non-medical school students compared to medical students, a similar trend was observed in the conducted study (when comparing students of scienti c and non-scienti c curriculums). 34% of high school students consider alcohol to be an oral cancer risk factor and 22% say that HPV infections have an impact on HNCs development [13]. Similarly, in the opinion of 32.9% of standard high school students and 21.5% of technical school students from the study population, alcohol can in uence the development of cancer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A total of 11.6% of participants were unaware of the term "HNCs". In contrast with studies carried out in Poland and Ireland, where 14.8% and 70% of the population were unfamiliar with HNCs, our numbers were noticeably superior [11,12]. This can be attributed to the documentation of higher risk in our geographical zone, advanced stage presentation and inadequate treatment facilities [2].…”
Section: Discussioncontrasting
confidence: 92%
“…This is in line with the finding of another study, in which people older than 65 years had heard of HPV significantly less than the younger generations ( p = 0.001) [ 16 ]. Still, levels of HPV and HPV-OPSCC awareness as well as HPV vaccination in young populations are alarmingly low [ 19 , 20 ]. In an online survey on head and neck cancer, which was conducted amongst 1,903 subjects aged 18–35 years in Poland, the overall awareness for HPV as a causative agent for head and neck cancer was only 37.2% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%